Will Nitrogen fixers benefit from rising Atmospheric CO2? The response of Podalyria Sericea to elevated CO2 - Swemmer, Tony (Department of Environmental and Geographical Science, 2021)
To predict the response of communities and ecosystems to rising levels of atmospheric CO2, the response of individual plants under natural conditions needs to be determined. Podalyria sericea, a fynbos legume, was grown in a greenhouse under ambient (35 Pa) and elevated (70 Pa) CO2 partial pressure for 18 months. Growth, leaf 615N and leaf gas exchange was measured to determine whether this N2-fixer could maintain a positive growth response under conditions of high competition. Results revealed a lack of positive growth response to elevated CO2, although far more flowers were produced in the elevated treatment. Allocation patterns were slightly different, with relatively higher shoot mass for plants exposed to elevated CO2. Leaf 61 5N and N concentrations were unaffected. Photosynthetic capacity was greatly reduced and maximum rates of Rubisco carboxylation (V cmaJ and light saturated electron transport (Jniax) were lower for plants exposed to elevated CO2. Net CO2 assimilation (A) at growth CO2 was higher for the plants from the ambient treatment. Shading appears to have been an important constraint on growth response to elevated CO2, and plants which received more light had significantly more biomass in the elevated treatment. The potential effect of restricted root growth and low soil nutrient availability are discussed as additional factors which may have negated a positive growth response.